WOMEN POLITICIANS BASED ON PESANTREN IN NATIONALIST BASED VOTERS IN INDONESIA - Mokhamad Zainal Anwar; Khairul Imam; Abdulloh Hadziq; Wahyudi Akmaliyah; Yuyun Sunesti (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2022)
This study discusses the activism of pesantren-based female politicians in utilizing the pesantren network in electoral districts where most of constituents affiliate with nationalist-style parties. One of which is the Soloraya area. A portrait of post-reform electoral districts with solid political affiliations to nationalist parties. In this context, this study intends to examine the political activism of women politicians based on Islamic boarding schools in electoral politics. The data collected in this study carries out by observation and in-depth interviews. This study argues that the solidity of the santri and pesantren constituent bases, the expansion of the non-student voter base, the support of the pesantren elite, and the performance of female political candidates based on pesantren are the keys to the success of transforming social capital into political capital to win electoral politics in electoral districts that are not pesantren based. The novelty of the findings of this study is that female politicians can win electoral politics in the 2019 elections by mobilizing political disillusionment, militancy, and solidity in support of the pesantren network, especially among women and the social capital attached to individual politicians. This study enriches the study of electoral politics and its relationship to the activism of women politicians based on pesantren.